Systematic Study of Classification - Atherton, Pauline (Journal of Information and Knowledge, 1989)
Presents a review of the book Prolegomena to library classification. The exposition of the text is based on a set of levels of normative principles. This helps in teaching library classification as well as in clear thinking about the subject. The five inherent concepts of scheme of classes - characteristic, succession of characteristics, array of classes, chain of classes, and filiatory sequence - are lucidly brought out. The mental separation of the theory of library classification into three planes - idea, verbal, and notational planes - helps the development of the theory of library classification. This is of immense help to students arid to teachers. Ranganathan's way of representing the structure and the development of the universe of subjects helps not only the classificationist but also the computer scientist struggling to arrange the graphic display of knowledge. Ranganathan's method of facet analysis of subjects contained in a document and in a reader's query will be of immense help for computer-based document retrieval systems, though he has not worked with a computer. The abstract model of library classification given in the book, helps a classificationist in reaching this ideal. On the whole, the edition 3 of the Prolegomena aids comparative study of classification by providing a systematic and clear exposition of the theory of library classification.